Isola : a novel [large type] - Goodman, Allegra (Random House Large Print, 2025)
"France, 1531. Orphaned by the age of five, Marguerite de la Rocque was heir to a chateau with its own village and lands. But her guardian, Jean Francois de la Rocque de Roberval, sells Marguerite's property to embark on an expedition to New France, bringing Margueriteand her maidservant with him. Aboard the ship, the women are limited to the company of the captain, the navigator, Roberval, and his secretary--a man whose musical talent, literary knowledge, and dark eyes intrigue Marguerite. It isn't long before the two of them are meeting secretly to declare their love for one another. When Roberval discovers this transgression, he is furious, seeing their affection as betrayal. As punishment, he maroons them on a small island off thecoast, condemning them to certain death"--